The infalling photon, the infalling particle, and the observer at rest near the horizon of a black hole - Mazzitelli, Francisco Diego (2020)
When a massive test particle or a photon fall radially into a black hole, their energy, as measured by a static observer located very close to the horizon, diverges. In introductory courses on general relativity, this fact gives rise to questions about the reality of this divergence and its eventual effect on the geometry of the black hole. We address these concerns and show that, eventually, it is the observer at rest who may induce corrections to the metric, unless its mass is crucially small when located near the horizon.